AL-QUR’AN DAN TAFSIR MEDIA : (Makna Hijrah Di Dalam Al-Qur'an Menurut Perspektif KH. Husain Muhammad Di Youtube) - Arifin, Miftakul; Rosyidah, Ainur; Mawaddah, Sufiyana Nur (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2023)
The Qur'an as a corpus is open to Muslims, so for the commentators of the Qur'an it continues to be studied and researched to find out its interpretation. The interpretation of the Qur'an itself continues to grow, initially the Qur'an was interpreted textually and contextually along with the development of the media, many commentators wrote interpretations by utilizing social media such as Facebook, Instagram, YouTube to enrich the scientific treasures of the interpretation of the Qur'an, as the interpretation of hijrah. Hijrah which is familiar in our society is very close to the story of the Prophet Muhammad, namely the migration from Mecca to Medina. However, along with the development of the hijrah era, which used to mean moving places now has a different interpretation and the meaning is getting wider. So it is necessary to do research and reinterpretation to antithesis of the old research that distorts the meaning of the Qur'an. This study aims to determine 1. The meaning of Hijrah in the perspective of the Qur'an. 2. Interpretation of verses about the Hijrah of the Qur'an Surah al Nahl, 16: 41 and Q.S. al Anfal 8:74 according to Kyai Husein Muhammad on Youtube. 3. The meaning of Hijrah according to Kyai Husein Muhammad on Youtube. The method used in this study uses a qualitative descriptive method of virtual studies, while the approach used is an interpretive approach. The findings show that the meaning of hijrah according to KH. Husein Muhammad on Youtube has 2 meanings, namely physically the meaning of hijrah is indeed defined by moving to another safer place, where Muslims can easily carry out their obligations to worship Allah and follow the Prophet's orders calmly, without interference from other people polytheists. While the literal meaning is a transfer that is not only in the body but in the heart, the mind that initially denied the authority of God Almighty and acted tyrannically moved towards the truth by acknowledging God's validity, leaving behind bad actions such as humiliating, intimidating others, lying, slandering, committing wrongdoing. fair to others in the sense of moving from actions that violate human norms to norms that are humanity and justice.